A taste of the Hocking Hills - Rapposelli, Matt (Ohio University Press, 2018)
A Taste of the Hocking Hills intermingles delicious recipes with striking photographs of the Appalachian region. Chef Matt Rapposelli presents dishes by the season, noting the specialties appearing on his menus that time of year. Whether enjoying a winter evening or a summer morning, cooks will be able to bring a bit of the Hocking Hills home.